Crystallization behavior of poly(lactide)/poly(β‐hydroxybutyrate)/talc composites. Issue 6 (25th February 2013) - Tri, Phuong Nguyen; Domenek, Sandra; Guinault, Alain; Sollogoub, Cyrille
Abstract The morphology and miscibility of commercial poly(lactide) (PLA)/poly(β‐hydroxybutyrate) (PHB, from 5 to 20 wt %) blends prepared by melt extrusion method, were investigated using differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FTIR) observations. The results show that for all the studied blend contents, PLA/PHB blends are immiscible. The effects of PHB and talc on the nonisothermal cold crystallization kinetics of PLA were examined using a differential scanning calorimetry (DSC) at different heating rates. PHB acted as a nucleating agent on PLA and the addition of talc to the blend yielded further improvement, since significant increase in the enthalpy peak was observed for samples containing 10 wt % PHB and talc (from 0.5 to 5 phr). The crystallization kinetics were then examined using the Avrami–Jeziorny and Liu–Mo approach. The simultaneous presence of PHB and talc induced a decrease of the crystallization half time. The evolution of activation energies determined with Kissinger's equation suggests that blending with PHB and incorporating talc promote nonisothermal cold crystallization of PLA. The synergistic nucleating effect of PHB and talc was also observed on isothermal crystallization of PLA from the melt. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013